Improving medical care and prevention in adults with congenital heart disease-reflections on a global problem-part I: development of congenital cardiology, epidemiology, clinical aspects, heart failure, cardiac arrhythmia - Neidenbach, Rhoia; Niwa, Koichiro; Oto, Oeztekin; Oechslin, Erwin; Aboulhosn, Jamil; Celermajer, David; Schelling, Joerg; Pieper, Lars; Sanftenberg, Linda; Oberhoffer, Renate; De Haan, Fokko; Weyand, Michael; et al. (Cardiovascular Diagnosis and Therapy, 2018)
Today most patients with congenital heart defects (CHD) survive into adulthood. Unfortunately, despite relevant residua and sequels, follow-up care of adults with congenital heart disease (ACHD) is not performed in specialized and/or certified physicians or centres. Major problems in the long-term course encompass heart failure, cardiac arrhythmias, heart valve disorders, pulmonary vascular disease, infective endocarditis, aortopathy and non-cardiac comorbidities. Many of them manifest themselves differently from acquired heart disease and therapy regimens from general cardiology cannot be transferred directly to CHD. It should be noted that even simple, postoperative heart defects that were until recently considered to be harmless can lead to problems with age, a fact that had not been expected so far. The treatment of ACHD has many special features and requires special expertise. Thereby, it is important that treatment regimens from acquired heart disease are not necessarily transmitted to CHD. While primary care physicians have the important and responsible task to set the course for adequate diagnosis and treatment early and to refer patients to appropriate care in specialized ACHD-facilities, they should actively encourage ACHD to pursue follow-up care in specialized facilities who can provide responsible and advanced advice. This medical update emphasizes the current data on epidemiology, heart failure and cardiac arrhythmia in ACHD.
EVALuna2:35958